Qalb (Virtue)-Guided Leadership in higher education institutions: strategy and sustainability - Hassan, Mohd. Kamal (2016)
Introduction The issue of leadership in higher education institutions has never become more challenging today than ever before, especially in Muslim countries, for several reasons, among which are the following: a) The failure of political and economic systems in many Muslim countries to provide stable, sustainable and long-lasting solutions to the problems of human development and nation-building, the quality of life for the people as a whole and the ability to overcome the negative impact of globalized capitalism and materialistic consumerist culture; b) The emergence of the “excellence without the soul syndrome” in many universities as a consequence of adopting the neo-liberal market oriented educational paradigm which emphasizes the commercialization and commodification of higher education. The fear expressed by several concerned educationists around the world that universities would succumb to the “cancer” of commercialization, due to the socioeconomic changes generated by the capitalistic hegemony, in the era of globalization has become a serious issue among intellectuals who are concerned with the crisis of higher education in the world today. In a technology-dominated economy universities may be forced to become incubators of new industries while the business of character development may have to be sidelined. Examples of some of the critical intellectual concerns are as follows: